Gilles Châtelet: elementi per una diagnostica del pensiero fisico-matematico (Nóema, 2025)
Gilles Châtelet: Elements for a diagnosis of physical-mathematical thoughtThis paper examines the epistemological thought of Gilles Châtelet and his contributions to the philosophie mathématique, a chapter of the European philosophy of science that is not well-known, but which in France has a long conceptual history centered on debates on the nature of mathematics and its close relationship with physics. This context, which found one of its greatest expressions in the works of Gaston Bachelard, includes the path of this figure who, in the second half of the twentieth century, enriched the French epistemological panorama by making the philosophy of mathematical physics a projet de pensée. This was possible because Châtelet examined some figures of mathematical thought read in the light of Naturphilosophie. for the importance given to what are called "intuitive practices" and to their way of constituting the physical-mathematical unity, considered strategic for philosophical reflection in grasping science as pensée tout court.
Keywords: French epistemology; Philosophie Mathématique; Châtelet; Philosophy of mathematical physics; Thought of sciences